Uji Daya Simpan dan Efektivitas Prototipe Pupuk Hayati Mikoriza dengan Media Pembawa Pasir Vulkanik dan Pasir Laut - KADEK JUNIARI; I NYOMAN RAI; I MADE SUKEWIJAYA (Fakultas Pertanian Universitas Udayana, 2020)
Time Storage and Effectivity of the Prototype of Mychorrhiza Biological Fertilizer with Volcanic and Sea Sand as the Carrier Media. This research aimed to study time storage and the efectivity of prototype of mychorrhiza biological fertilizer with volcanic and sea sand as the carrier media. The study was arranged using a randomized block design with 2 factors. The first factor was carrier media of mychorrhiza spore consist of 2 levels i.e. volcanic and and sea sand, and the second factor was time storage of prototype of mychorrhiza biological fertilizer consist of 3 levels i.e. 1, 2, and 3 month. The result of research showed that volcanic sand carrier media was better than the sea sand media proved by higher total dry weight. The best time storage of prototype of mychorrhiza biological fertilizer in this research was 1 month indicated by the highest amount of spores after storage. The interaction between carrier media and time storage gave significantly different just to stem diamater and fresh weight of corn cob.